Study on the wind uplift failure mechanism of standing seam roof system for performance-based design. (15th December 2020) - Wu, Tao; Sun, Ying; Cao, Zhenggang; Yu, Zhimin; Wu, Yue
Highlights: The characteristic-response changes of roof system during failure process are recorded by measuring instruments. The failure process of roof system is divided into three stages according to the change in interaction among components. The three-stage failure process is verified in combination with the changes in characteristic-response. Explain the damage in the experiment according to the deformation map of roof system. Analyze the relationship between failure stage and performance of roof system, so as to serve PBD. Abstract: Compared with the current popular performance-based design (PBD) method, the current research of scholars on structural performance as a PBD foundation is insufficient. By considering the failure process of a standing seam roof system as an example, the wind-resistant performance of a roof system is evaluated by studying the wind uplift failure mechanism. The deformation process of roof-system components is obtained using numerical simulations. The analysis shows that the interaction between the vertical plate and anti-wind clip occurs in three stages: from non-contact and no interaction to anti-wind clips restraint vertical plate deformation, and finally to vertical plates drive anti-wind clip rotation. The changes in the structural responses (seam displacement and contact stress) and damage during the failure process of the roof system are obtained through experiments. Analysis of the variation in the curve of the structural responses with the load shows that the increase in the structural responses also occurs in three stages. Combined with the damage sequence, the aforementioned three failure stages are found to correspond to three different damage stages. In the first stage, the roof system is in an elastic stage. Second, the roof system is in the yield stage, and curling undergoes partial separation, which results in an interspace that is adverse to roof waterproofing. In the third stage, permanent plastic deformation occurs in the roof system, which leads to roof ponding. It was observed that the three-stage failure process represents different performance levels of the roof system, and some results from this study can be used as a guide for the definition of roof-system performance level in the future.